Development of a Reciprocal Health Care Model for Determination of Safety Level in the Nursing Homes in Estonia - Sepp, Jaana (European Journal of Economics and Business Studies, 2018)
The aim of the current paper was to assess the care workers’ psychosocial and physical health; patient’s safety and examine the variations of care workers’ working conditions in the national nursing homes. The NOSACQ-50 questionnaire was used as a research method. The majority of the care workers in nursing homes complain about physical pain, especially low back pain, and work-related stress. The study results show, that several specific features, such as management safety priority, commitment and ability, are found to influence the six dimensions of safety climate. Based on these results, the importance of good communication practices, management commitment and effective safety training to ensure a strong safety climate and safe behaviour among health care workers is highlighted. Mutual support from the employers to the care workers is needed to create safety as an organizational value. Thus, an effective assessment tool for the evaluation of safety level in nursing homes could be proposed based on the results of this study. The current paper presents a Reciprocal Health Care Model for determination the levers of safety improvement in nursing homes. The model refers to the importance of management safety priority and abilities as well as peer safety communication and trust in the safety ability.